Modeling and dynamic simulation of a hybrid liquid desiccant system with non-adiabatic falling-film air-solution contactors for air conditioning applications in buildings - Prieto, Juan; Atienza-Márquez, Antonio; Coronas, Alberto (MDPI, 2021)
This paper presents an experimentally validated, dynamic model of a hybrid liquid desic-cant system. For this purpose, we developed new components for the air-solution contactors, which are of the non-adiabatic falling-film type with horizontal tubes (made of improved polypropylene) and the solution tanks. We also provide new experimental correlations for both the tube-solution heat transfer coefficient and the mass transfer coefficient on the airside as a function of the air velocity. To validate the model, the results obtained from the dynamic simulations were compared with those obtained by monitoring a demonstration unit installed in a sports center in Taipei (Taiwan). Once validated, the model was used to perform a sensitivity analysis at different operational conditions, such as the inlet water temperatures in the air-solution contactors and the LiCl mass fraction at which the system operates. The results of the sensitivity analysis were used to optimize the seasonal performance in terms of comfort and energy required by the system. Compared with a conventional air-handling unit that controls air temperature and humidity, the annual energy savings of the liquid desiccant systems are 17%.
Keywords: Aire acondicionado; Air conditioning; Dynamic modeling; Experimental validation; Falling film air-solution; Hybrid liquid desiccant system; Multi-objective optimization